Empowering women, challenging caste? The experience of a dairy cooperative in India - Farnworth, Cathy Rozel; Bharati, P.; Galiè, Alessandra (Frontiers Media, 2023)
The empowerment of women in agri-food systems is essential to enhance the well-being of women and their households, reduce hunger, boost incomes and strengthen resilience. The empowerment of women in the livestock sector is key to the progress of the sector. Livestock in turn provide a unique entry point to support the empowerment of women. Yet evidence shows that in low and middle income countries (LMIC) gender discriminatory norms and practices reduce the ability of women in livestock to rear and maintain healthy and productive animals, as well as to access the markets needed to obtain income. Cooperatives are one mechanism for overcoming some of these constraints. Yet, little is known on the extent to which women’s empowerment can be supported through cooperatives in the livestock sector. In this paper we studied how membership in Mulukanoor Dairy had changed gender dynamics within households. Caste was selected as a significant cross-cutting variable that affects power dynamics in interaction with gender. The study therefore also analyzed how Mulukanoor Dairy improved caste relations between members, and whether gender relations have changed in similar ways across households belonging to different castes. We framed our study in a conceptual framework structured around six concepts of power; power with, power over, power within, power to act, power to empower, power through, and a related concept termed a gender norms façade. Focus group discussions and Key informant interviews were held with women members of Mulukanoor in caste-based groups. The findings show that gender norms are quite fluid while caste norms are less so thereby differentially affecting the ability of Mulukanoor as an organisation, and women members in different castes, to achieve various forms of empowerment. Despite these differentials, Mulukanoor has radically shifted gender relations in dairy.